Sundanese Language Maintenance Based on The Heterogeneity of The Speakers - Siti Junawaroh; Cece - Sobarna; Wahya - -; Sugeng - Riyanto (PAROLE: Journal of Linguistics and Education, 2020)
The issue of maintaining the Sundanese Brebes language in the Sundanese community in Brebes Regency was raised because the existence of the Sundanese Brebes language is potentially threatened economically, socially, and politically by Javanese, Indonesian, and foreign languages. Previous studies suggest that monolingual communities are vulnerable to switch to languages with higher political power, whereas established multilingual communities tend to survive. However, this is different from the Sundanese Brebes language. The purpose of this paper is to examine the pattern of Sundanese Brebes maintenance based on heterogeneity. The number of respondents in this study was 400. The results of the analysis showed that monolingual communities type 1 and 2 maintain Sundanese Brebes language more active than multilingual communities type 3 and 4. In the monolingual community, the presence of Javanese and Indonesian languages with dominant economic and political power did not influence significantly language maintenance. In contrast, the maintenance of Sundanese Brebes in the multilingual community is more passive. The maintenance of Sundanese Brebes still occurs because of the strong identity of Sundanese Brebes. This study is expected to contribute to the study of language maintenance patterns in several community characteristics.